Detection of Pathogens, Indicators, and Antibiotic Resistance Genes after Land Application of Poultry Litter. Issue 5 (1st September 2014) - Cook, K. L.; Netthisinghe, A. M. P.; Gilfillen, R. A.
Abstract : Poultry litter (PL) is a by‐product of broiler production. Most PL is land applied. Land‐applied PL is a valuable nutrient source for crop production but can also be a route of environmental contamination with manure‐borne bacteria. The objective of this study was to characterize the fate of pathogens, fecal indicator bacteria (FIB), and bacteria containing antibiotic resistance genes (ARGs) after application of PL to soils under conventional till or no‐till management. This 2‐yr study was conducted in accordance with normal agricultural practices, and microbial populations were quantified using a combination of culture and quantitative, real‐time polymerase chain reaction analysis. Initial concentrations of Campylobacter jejuni in PL were 5.4 ± 3.2 × 10 6 cells g −1 PL; Salmonella sp. was not detected in the PL but was enriched periodically from PL‐amended soils. Escherichia coli was detected in PL (1.5 ± 1.3 × 10 2 culturable or 1.5 ± 0.3 × 10 7 genes g −1 ) but was rarely detected in field soils, whereas enterococci (1.5 ± 0.5 × 10 8 cells g −1 PL) were detected throughout the study. These results suggest that enterococci may be better FIB for field‐applied PL. Concentrations of ARGs for sulfonamide, streptomycin, and tetracycline resistance increased up to 3.0 orders of magnitude after PL application and remained above background for up to 148 d. These data provide new knowledge about important microbial FIB, pathogens, and ARGs associated with PL application under realistic field‐based conditions.